Perkuliahan berbasis Riset pada Pendidikan Kimia: Karakteristik, Implementasi, dan Impak - Lukman Hadi; Ahmad Mudzakir; Yuli Rahmawati (Postgraduate, University of Mataram, 2025)
Course-Based Undergraduate Research Experiences (CUREs) have gained increasing prominence as an innovative pedagogical model that integrates authentic research into the undergraduate curriculum. While extensive research has highlighted the general benefits of CUREs across STEM fields, a focused synthesis of their implementation and impact specifically within chemistry education remains underexplored. This narrative review addresses this gap by analyzing ten recent, peer-reviewed studies indexed in Scopus to characterize how CUREs are designed, implemented, and evaluated in undergraduate chemistry contexts. The findings demonstrate that CUREs shift traditional laboratory instruction toward inquiry-based, authentic research experiences that foster critical thinking, increase student engagement, and enhance retention in STEM, especially within inclusive learning environments. However, challenges such as faculty workload, scalability, and research output persist. By consolidating insights across current literature, this review contributes a field-specific understanding of CUREs in chemistry education and offers implications for curriculum design, institutional support, and future research directions. In doing so, it fills a critical gap in the literature and underscores the evolving role of CUREs in preparing the next generation of chemists through evidence-based, research-intensive teaching practices.